Is lower training frequency more effective? Dose-response relationship of in-season flywheel resistance training on vertical jump and sprint performance in male team-sport athletes: a meta-analysis - Qu, W.; Lu, D.; Sun, X.; Sun, J.; He, J.; Song, W.; Li, D. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Objective The purpose of this study is to systematically review and meta-analyze the effects of in-season flywheel resistance training (FRT) compared to traditional resistance training (TRT) on vertical jump and linear sprint performance in team-sport athletes. Additionally, this study aims to explore the moderating effects of training parameters (such as frequency, intensity, and duration) on training outcomes.